Exploring resistance to implementation of welfare technology in municipal healthcare services – a longitudinal case study. Issue 1 (December 2016) - Nilsen, Etty; Dugstad, Janne; Eide, Hilde; Gullslett, Monika; Eide, Tom
Abstract Background Industrialized and welfare societies are faced with vast challenges in the field of healthcare in the years to come. New technological opportunities and implementation of welfare technology through co-creation are considered part of the solution to this challenge. Resistance to new technology and resistance to change is, however, assumed to rise from employees, care receivers and next of kin. The purpose of this article is to identify and describe forms of resistance that emerged in five municipalities during a technology implementation project as part of the care for older people. Methods This is a longitudinal, single-embedded case study with elements of action research, following an implementation of welfare technology in the municipal healthcare services. Participants included staff from the municipalities, a network of technology developers and a group of researchers. Data from interviews, focus groups and participatory observation were analysed. Results Resistance to co-creation and implementation was found in all groups of stakeholders, mirroring the complexity of the municipal context. Four main forms of resistance were identified: 1) organizational resistance, 2) cultural resistance, 3) technological resistance and 4) ethical resistance, each including several subforms. The resistance emerges from a variety of perceived threats, partly parallel to, partly across the four main forms of resistance, such as a) threats to stability and predictability (fear of change), b) threats to role and group identity (fear of losing power or control) and c) threats to basic healthcare values (fear of losing moral or professional integrity). Conclusion The study refines the categorization of resistance to the implementation of welfare technology in healthcare settings. It identifies resistance categories, how resistance changes over time and suggests that resistance may play a productive role when the implementation is organized as a co-creation process. This indicates that the importance of organizational translation between professional cultures should not be underestimated, and supports research indicating that focus on co-initiation in the initial phase of implementation projects may help prevent different forms of resistance in complex co-creation processes.